2017
DOI: 10.1061/(asce)ei.1943-5541.0000317
|View full text |Cite
|
Sign up to set email alerts
|

Undergraduate Geotechnical Engineering Education of the 21st Century

Abstract: interests" (Marcuson et al. 1991). Unfortunately, the current geotechnical education curriculum 16 does not provide the foundation necessary to ensure the engineer's success in the 21 st century. A typical academic year in universities is divided into several (e.g., two, three, four or more) 103 teaching semesters, terms, or quarters. The introductory geotechnical course varies from university 104 to university, though it often includes a laboratory section to gain practical experience in soil 105 testing and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Further, this study also highlighted the importance of incorporating practical experience and real-world applications into coursework in GEE for active learning. Wirth et al (2016) discussed the need for interdisciplinary education and the incorporation of new technologies and methods, as well as the importance of practical experience and hands-on learning opportunities in GEE [7]. Jiang et al (2021) highlighted the need for continued innovation in GEE to ensure that students receive a high-quality education in the face of COVID-19 disruptions [1].…”
Section: Overview Of Geotechnical Engineering Educationmentioning
confidence: 99%
“…Further, this study also highlighted the importance of incorporating practical experience and real-world applications into coursework in GEE for active learning. Wirth et al (2016) discussed the need for interdisciplinary education and the incorporation of new technologies and methods, as well as the importance of practical experience and hands-on learning opportunities in GEE [7]. Jiang et al (2021) highlighted the need for continued innovation in GEE to ensure that students receive a high-quality education in the face of COVID-19 disruptions [1].…”
Section: Overview Of Geotechnical Engineering Educationmentioning
confidence: 99%
“…Students often found it difficult to understand explicitly the importance of subsurface conditions in constructing highway systems or building skyscrapers. Besides, large uncertainties in GGE can easily confuse and upset students as compared with other more prescribed disciplines (Wirth et al, 2017). The implicitness and uncertainty of GGE, when delivered in the traditional chalk-and-talk lecture style, have already made many students, even in normal times, conclude that learning soil mechanics, foundation engineering and geoenvironmental engineering is boring, if not outdated.…”
Section: Introductionmentioning
confidence: 99%
“…A publication by Reference [87] revealed that "Flow in Porous Media" [71] also known as mechanics of porous media [4], is one of the most essential modules in the course system for undergraduate education in petroleum engineering. This is because, it mainly deals with the study of the manner in which fluids, such as oil, gas, water, and so on, behave when flowing through a porous media (reservoir).…”
Section: Introductionmentioning
confidence: 99%